Diagnostic yield of bronchoalveolar lavage in immunocompromised children with malignant and non‐malignant disorders. Issue 6 (3rd January 2017) - Nadimpalli, Sruti; Foca, Marc; Satwani, Prakash; Sulis, Maria Luisa; Constantinescu, Andrei; Saiman, Lisa
Summary: Background: The diagnostic yield of bronchoalveolar lavage (BAL) in the Immunocompromised pediatric population has ranged from 28% to 68%. We hypothesized that the diagnostic yield of BALs would be higher in more recent years due to new diagnostic assays. Methods: A retrospective case series was performed among immunocompromised children ≤18 years old who underwent BALs from 2001 to 2012, to assess the yield of microbiologic diagnostic studies and to determine the impact of BAL findings on antimicrobial management. Results: In all, 123 subjects underwent 174 BALs (mean age 9.9 years). Underlying diagnoses included both malignant (n = 79) and non‐malignant (n = 44) disorders, and 75 (61.0%) subjects were hematopoietic stem cell transplant (HSCT) recipients. Fifty‐four (31.0%) of 174 BAL were positive for ≥1 potential pathogen (n = 58 microorganisms). The diagnostic yield of BALs performed from 2001 to 2006 versus2007–2012 was similar (40.5% vs. 26.6%, respectively, P = 0.07). Most subjects (86.2%) were on ≥1 antimicrobial at the time of BAL. Most (65.8%) negative BALs were associated with narrowing antimicrobial therapy, while most (74.1%) positive BALs were associated with continuing or changing to targeted antimicrobial therapy. Conclusions: In this study population, the diagnostic yield of BAL was similar to that previously described and unchanged in more recent years. Both negative and positive BALs were associated with changes in antimicrobial management. Summary: A 10‐year retrospective review of bronchoalveolar lavage in 123 immunocompromised children determined that the rate of isolation of potential pathogens was 31% in this population. The majority of BAL was associated with a change in antimicrobial therapy.Pediatr Pulmonol. 2017;52:820–826. © 2017 Wiley Periodicals, Inc.